2020
DOI: 10.1073/pnas.2004018117
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated reproduction is not an adaptive response to early-life adversity in wild baboons

Abstract: In humans and other long-lived species, harsh conditions in early life often lead to profound differences in adult life expectancy. In response, natural selection is expected to accelerate the timing and pace of reproduction in individuals who experience some forms of early-life adversity. However, the adaptive benefits of reproductive acceleration following early adversity remain untested. Here, we test a recent version of this theory, the internal predictive adaptive response (iPAR) model, by assessing wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 100 publications
(193 reference statements)
5
69
2
Order By: Relevance
“…Moreover, a recent study on yellow baboons (Papio cynocephalus) demonstrated that the fitness effects of a longer life far outweigh the fitness effects of an accelerated reproductive schedule. 52 This opens the door to a third hypothesis: that male-mediated maturation is not adaptive but simply the Please cite this article in press as: Lu et al, Male-Mediated Maturation in Wild Geladas, Current Biology (2020), https://doi.org/10.1016/ j.cub.2020.10.003 Report byproduct of selection for females to retain sensitivity to new breeding males. Specifically, the Bruce effect (male-mediated pregnancy loss) can mitigate the costs of infanticide across the life course.…”
Section: Reportmentioning
confidence: 99%
“…Moreover, a recent study on yellow baboons (Papio cynocephalus) demonstrated that the fitness effects of a longer life far outweigh the fitness effects of an accelerated reproductive schedule. 52 This opens the door to a third hypothesis: that male-mediated maturation is not adaptive but simply the Please cite this article in press as: Lu et al, Male-Mediated Maturation in Wild Geladas, Current Biology (2020), https://doi.org/10.1016/ j.cub.2020.10.003 Report byproduct of selection for females to retain sensitivity to new breeding males. Specifically, the Bruce effect (male-mediated pregnancy loss) can mitigate the costs of infanticide across the life course.…”
Section: Reportmentioning
confidence: 99%
“…Based on a recent analysis on female maturations for this population [ 65 ], we expect that females in small units will have later ages at maturation and first birth to avoid inbreeding (since their fathers have longer tenures), and we expect that females in large units will have earlier ages at maturation and first birth due to the ‘Vandenbergh effect’ that accompanies male takeovers. However, even if these predictions are supported in future analyses, we do not expect these unit size differences to significantly alter our reproductive success estimates for two reasons: first, the observed range in age at first birth in this population is narrow [ 57 ], and second, in similarly long-lived primates, age at first birth had a very modest impact on variation in lifetime fitness [ 66 , 67 ]. Future analyses that address the potential for different female reproductive strategies, which require more complete female lifespans than we have currently, will allow us to determine the effects of unit size on realized lifetime reproductive success.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons might explain why offspring survival might be prioritized over maternal reproductive pace. First, lifespan and offspring survival are the primary components of female lifetime reproductive success in long-lived species such as baboons, while reproductive pace may be less important [52]. Second, shorter IBIs might compromise infant survival independently of the effect of birth timing and are thus not necessarily adaptive [7].…”
Section: Discussionmentioning
confidence: 99%